2019
DOI: 10.14233/ajchem.2019.21569
|View full text |Cite
|
Sign up to set email alerts
|

Self Emulsifying Drug Delivery System: A Recent Approach

Abstract: In recent years, nearly 40 % newer drugs compounds are hydrophobic in nature, which is a major challenge now-a-days for oral drug delivering due to low aqueous solubility. Lipid based drug delivery system is one of the favourable approach for poorly soluble compounds which can improve the drug absorption and oral bioavailability. Due to ion-pairing with appropriate surfactant and co-surfactant the macromolecular drug molecular oil droplet being found in the gut flow oral absorption which sufficiently stable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
1
2
0
Order By: Relevance
“…Increased surface area of the SLMs through globules formulation r the absorption of the drug molecule, led to enhanced intestinal permeability thus resulting in improved bioavailability and subsequent reduction in parasitemia. These findings in improved bioavailability collaborated the work of Bindhani et al 40 Literatures have shown that the bioavailability of artemetherlumefantrine increases with the administration of milk or fatty meals. 8 The formulation of artemether-lumefantrine in fatty microparticles could have improved its bioavailability as the solid lipid microparticles could have protected the entrapped artemetherlumefantrine from degradation.…”
Section: In Vivo Studiessupporting
confidence: 76%
“…Increased surface area of the SLMs through globules formulation r the absorption of the drug molecule, led to enhanced intestinal permeability thus resulting in improved bioavailability and subsequent reduction in parasitemia. These findings in improved bioavailability collaborated the work of Bindhani et al 40 Literatures have shown that the bioavailability of artemetherlumefantrine increases with the administration of milk or fatty meals. 8 The formulation of artemether-lumefantrine in fatty microparticles could have improved its bioavailability as the solid lipid microparticles could have protected the entrapped artemetherlumefantrine from degradation.…”
Section: In Vivo Studiessupporting
confidence: 76%
“…Medicines: A large number of herbal drugs and traditional medicines are being exploited and used for the development of SMEDDS because most of them have volatile and fixed oils 34,35 .…”
Section: Smedds For Herbal Drugs and Traditionalmentioning
confidence: 99%
“…Oral drug delivery is the most convenient and preferable route for administration of drugs because of low cost and easy administration (Bindhani et al, 2019). The oral route is the preferred route for chronic drug therapy.…”
Section: Introductionmentioning
confidence: 99%